2016
DOI: 10.35791/eug.22.2.2016.12956
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring Dampak Ekologis Merkuri Di Daerah Aliran Sungai Toraut Kabupaten Bolaang Mongondow

Abstract: Traditional gold mining in Toraut Watershed Bolaang Mongondow District was used Merkuri Amalgamation that produced tailing. Tailing are discharged to river and environment sorounding that can enter Toraut River and flows to the down stream Mongondow river (beach Inobonto). This study aims: 1) To determine Hg concentrations in River Toraut up stream, middle stream and down stream; 2) To determine Hg concentrations in sediment of the River Toraut up stream, middle stream and down stream; 3) To determine Hg conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The waste disposed by the gold miners after the amalgamation process to the river without any treatments will cause water source, river, and seawater pollutions. The ecological impact of Hg in Toraut watershed, Bolaang Mongondow District reported that Hg was found in river water (< 0.00005 mg/ L), river sediment (<0.05-1.45 mg/kg), and water plant tissue (<0.001-0.013 mg/kg) [3]. The water in mining area such as Lanut Village had a Hg content at 0.0004-0.0012 mg/ L. Moreover, this study also found that the Hg content in the community (hair) was 0.171 -2.08 µg/g [4].…”
Section: Introductionmentioning
confidence: 99%
“…The waste disposed by the gold miners after the amalgamation process to the river without any treatments will cause water source, river, and seawater pollutions. The ecological impact of Hg in Toraut watershed, Bolaang Mongondow District reported that Hg was found in river water (< 0.00005 mg/ L), river sediment (<0.05-1.45 mg/kg), and water plant tissue (<0.001-0.013 mg/kg) [3]. The water in mining area such as Lanut Village had a Hg content at 0.0004-0.0012 mg/ L. Moreover, this study also found that the Hg content in the community (hair) was 0.171 -2.08 µg/g [4].…”
Section: Introductionmentioning
confidence: 99%